Teacher education and drama: possibilities, promise, potential. - Anderson, Elizabeth (Journal of the Canadian Association for Curriculum Studies, 2015)
Contemporary discussions about curricula, whether for schools or for higher education, come with demands for change to cope with uncertainty, unpredictability, and 21st century challenge. Core notions however of curriculum as structure for providing access to knowledge (Young, 2014), or a set of teaching and learning prescriptions (Scott, 2014) are hard to shift, yet questions of what knowledge and how is it formed are ones which should be critical for teacher education, where, as a site of higher education, decisions about that knowledge are contested (Barnett, 2015). The prospective teacher continues to negotiate tensions between knowledge of content and of curriculum, pedagogical knowledge and generic teaching skill, knowing as process and knowing in performative terms, and between shaping a role as teacher and as educator for the 21st century. This paper makes a case for the potential that an arts oriented course, specifically drama, holds for helping student teachers to conceptualise their own learning experiences within a teacher education curriculum, to better understand the facilitation of learning experiences within school and classroom curricula, and to begin to shape their teacher identity.